Respuestas
Respuesta dada por:
1
Respuesta:x=0, x=-4
Explicación paso a paso:
3x^2+6x=-6x
3x^+6x+6x=-6x+6x
3x^2+12x=0
X(1,2)=-12+-raizcuadrada de(12)^2-4*3*0/2*3
X(1,2)=-12+-12/2*3
X1=12+-12/2*3 x2=12+-12/2*3
X1=-4 x2=0
Respuesta dada por:
0
Respuesta:
4 x2=0
Explicación paso a paso:
3x^2+6x=-6x
3x^+6x+6x=-6x+6x
3x^2+12x=0
X(1,2)=-12+-raizcuadrada de(12)^2-4*3*0/2*3
X(1,2)=-12+-12/2*3
X1=12+-12/2*3 x2=12+-12/2*3
X1=-3x^2+6x=-6x
3x^+6x+6x=-6x+6x
3x^2+12x=0
X(1,2)=-12+-raizcuadrada de(12)^2-4*3*0/2*3
X(1,2)=-12+-12/2*3
X1=12+-12/2*3 x2=12+-12/2*3
X1=-4 x2=0
Preguntas similares
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años